2017
DOI: 10.3390/ph10020038
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Pharmaceutical Preparations of Chondroitin Sulfate Combined with Glucosamine

Abstract: Glycosaminoglycans are carbohydrate-based compounds widely employed as nutraceuticals or prescribed drugs. Oral formulations of chondroitin sulfate combined with glucosamine sulfate have been increasingly used to treat the symptoms of osteoarthritis and osteoarthrosis. The chondroitin sulfate of these combinations can be obtained from shark or bovine cartilages and hence presents differences regarding the proportions of 4- and 6-sulfated N-acetyl β-d-galactosamine units. Herein, we proposed a systematic protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
1
28
0
3
Order By: Relevance
“…At relatively high concentrations, glucosamine has been shown to have a protective effect on cartilage and synovial fluid; however many clinical trials have shown that this substance is unable to reach the tissue that it is meant to affect in appropriate and sufficient doses [68]. Structural heterogeneity of chondroitin sulphate, another supplement commonly taken alongside glucosamine, means that it is difficult to see consistent effects of this supplement, and the supplements available on the market are unlikely to be pure due to contamination with other glycosaminoglycans during the manufacturing process [71]. There is some evidence that glucosamine and chondroitin sulphate together provide superior effects on the inhibition of nitric oxide and prostaglandin synthesis and on protection of cartilage structure, than when applied alone [72,73].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…At relatively high concentrations, glucosamine has been shown to have a protective effect on cartilage and synovial fluid; however many clinical trials have shown that this substance is unable to reach the tissue that it is meant to affect in appropriate and sufficient doses [68]. Structural heterogeneity of chondroitin sulphate, another supplement commonly taken alongside glucosamine, means that it is difficult to see consistent effects of this supplement, and the supplements available on the market are unlikely to be pure due to contamination with other glycosaminoglycans during the manufacturing process [71]. There is some evidence that glucosamine and chondroitin sulphate together provide superior effects on the inhibition of nitric oxide and prostaglandin synthesis and on protection of cartilage structure, than when applied alone [72,73].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Once it had been determined that Stains‐all stains each GAG with distinct colors, we investigated whether this dye is useful in identifying particular GAGs present in mixtures with basis on their colors only. To avoid the usual contaminations found in raw extracts of sulfated polysaccharides such as DNA and proteins, we opted to prepare mixtures using standard GAGs as they are found in some common biomedical or pharmacological cases: hyaluronic acid and chondroitin 6‐sulfate as found in mammal cartilages ; chondroitin 6‐sulfate and keratan sulfate as found in pharmaceutical preparations of chondroitin sulfate from shark cartilages and dermatan sulfate and heparan sulfate (substituted here by heparin) as found in the urine of mucopolysaccharidosis‐I patients . In the first mixture both hyaluronic acid and chondroitin 6‐sulfate were easily distinguished by their bright‐blue and reddish‐brown colors, respectively, and also by their distinct electrophoretic mobility, that is because the high molecular weight hyaluronic acid ( M r >1.0 × 10 6 ) stays concentrated in the origin while the chondroitin 6‐sulfate ( M r ∼60 000) migrates as a polydisperse blot along the upper portion of the gel (Fig.…”
mentioning
confidence: 99%
“…Taken together, our UV-based spectroscopy confirmed the presence of GAGs, but could not distinguish their types. Further study of the GAGs found here using magnetic resonance spectroscopy (NMR) or disaccharide analyses should be performed (Santos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%